Design Principles and Methods for Distributed Business Intelligence Ecosystem - Kisimov, Valentin; Stefanova, Kamelia (Research Papers, 2010)
The paper is dedicated to a new approach in the scientific research, oriented towards Distributed Business Intelligent Ecosystems. This system is designed based on Distributed Business Intelligence Competence Centre. For the needs of Small and Medium Enterprises, the system is designed as a distributed. Three principles of distribution are presented – Principle of Horizontal distribution, Principle of Vertical distribution and the principle of Embedded distribution. A Design Framework is created on their basis, for the purpose of design of the following methods – Method for distribution of Data Warehouses, Method for distribution of OLAP engines, Method for distribution of Data Mining engines, and Method for distribution of Dashboards.